Effects of deep breathing on dynamic balance in patients with chronic mechanical low back pain - Abdelsalam, Mohammed Shawki; Afify, Amira Mohamed; Gaber, Heba Mohamed; Ibrahim, Saied Mohamed (SPORT TK-EuroAmerican Journal of Sport Sciences, 2026)
The diaphragm serves a dual role as the primary muscle of respiration and a core muscle that contributes to postural control. It is important to optimize both roles. However, in cases of low back pain (LBP), this optimization is compromised due to alterations in respiratory patterns in patients with chronic mechanical low back pain (CMLBP). The literature has not confirmed whether a deep breathing pattern (DBP) might enhance the diaphragm’s postural control function in patients with CMLBP. Primarily, this study investigated whether DBP might improve dynamic balance in patients with CMLBP. Secondarily, it examined differences in dynamic balance between patients and healthy subjects using DBP versus their spontaneous breathing pattern (SBP), as well as the correlation between pain and dynamic balance in the patient group across both breathing patterns. Dynamic balance was assessed in 15 patients with CMLBP and 15 matched healthy subjects during DBP and SBP. Patients with CMLBP significantly improved their dynamic balance when using DBP. However, healthy subjects showed enhanced dynamic balance using either breathing pattern. Furthermore, pain did not significantly correlate with dynamic balance control in the CMLBP group. It is recommended to encourage DBP in patients with CMLBP, as it may enhance dynamic balance, probably by emphasizing the diaphragm’s postural role.